2010
DOI: 10.1002/asi.21307
|View full text |Cite
|
Sign up to set email alerts
|

National study of information seeking behavior of academic researchers in the United States

Abstract: As new technologies and information delivery systems emerge, the way in which individuals search for information to support research, teaching, and creative activities is changing. To understand different aspects of researchers' information-seeking behavior, this article surveyed 2,063 academic researchers in natural science, engineering, and medical science from five research universities in the United States. A Web-based, in-depth questionnaire was designed to quantify researchers' information searching, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
86
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 41 publications
11
86
0
1
Order By: Relevance
“…They concluded that "differences in information-seeking behavior among universities are not as clear as among disciplines and demographics." 40 All of these user studies show a general adoption of Google among students and researchers alike.…”
mentioning
confidence: 99%
“…They concluded that "differences in information-seeking behavior among universities are not as clear as among disciplines and demographics." 40 All of these user studies show a general adoption of Google among students and researchers alike.…”
mentioning
confidence: 99%
“…This is in accordance with the fi ndings of earlier studies 51 be the most reliable way to ensure that OA journal content can be found and used. 19,52 The analyzed citation distribution pattern of OA journals in India confi rms the existence of a skewed citation distribution across the model and subjects, emphasizing that they are witnessing a considerable inequality in terms of their citation amount relative to their outputs within a single discipline, among disciplines, and within the whole OA journal subsystem. OA scientifi c publications are expected to gain a higher visibility, and their usability or infl uence is characterized partially by their supposedly higher citation rates; 27,54 at this point, however, this cannot be considered the case for OA journals being published from India.…”
Section: Discussionmentioning
confidence: 92%
“…19 Thomson Reuters and Elsevier index a limited number of journals in WoS and SCOPUS, respectively. Our results show that only a small percentage of green and a very low percentage of gold OA journals are included in these indexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical/doctoral institutions with very high research activity probably also have very rich serials collections, and thus there may be little need for articles to be ordered. In addition, studies on the informationseeking behaviors of scientists indicate that researchers use a variety of ways to obtain journal articles, including personal subscriptions and obtaining copies from colleagues, 56 behaviors that may be more common among well-connected and wellfunded researchers in medical/doctoral institutions with large research grants. It should also be noted that this correlation is for a very small number of institutions; thus, a few institutions with high research activity and very rich collections that have low ILL percent copies activity could contribute to the negative correlation.…”
Section: Effects Of Other Resource-sharing Initiativesmentioning
confidence: 99%